2015
DOI: 10.1080/00202967.2015.1117258
|View full text |Cite
|
Sign up to set email alerts
|

Tin whisker mitigation by means of a post-electroplating electrochemical oxidation treatment

Abstract: There are very few studies that have investigated directly the effect of an oxide film on tin whisker growth, since the 'cracked oxide theory' was proposed by Tu in 19941 . The current study has investigated the effect of an electrochemically produced oxide on tin whisker growth, for both Sn-Cu electrodeposits on Cu and pure Sn electrodeposits on brass. X-ray photoelectron spectroscopy (XPS) has been used to investigate the effect of the applied electrochemical oxidation potential on the oxide film thickness. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…For the thermally treated sample, the intermetallic compound was relatively uniform in thickness, whilst that present in the untreated control sample was much less regular and varied greatly in thickness, which is consistent with previous analyses of Sn-Cu deposits stored at room temperature. 30,31 The morphology of the IMC present within the ALD processed Sn-Cu coating from batch 4 (Fig. 12c) was similar to that of the thermally processed sample.…”
Section: Thermally Treated Control Samples (Batch 13)mentioning
confidence: 63%
See 1 more Smart Citation
“…For the thermally treated sample, the intermetallic compound was relatively uniform in thickness, whilst that present in the untreated control sample was much less regular and varied greatly in thickness, which is consistent with previous analyses of Sn-Cu deposits stored at room temperature. 30,31 The morphology of the IMC present within the ALD processed Sn-Cu coating from batch 4 (Fig. 12c) was similar to that of the thermally processed sample.…”
Section: Thermally Treated Control Samples (Batch 13)mentioning
confidence: 63%
“…These results suggest that the ALD coating itself may act as a physical barrier to impede whisker growth, as shown by previous studies that have investigated the influence of applied surface oxides on whisker growth. 31,35,36 ALD processing may, therefore, provide greater long-term whisker mitigation than thermal treatment alone, which may simply retard the onset of whisker growth. Longer-term monitoring of whisker growth will more clearly elucidate the benefits of the ALD coating.…”
Section: Summary Of Whisker Growth Trialsmentioning
confidence: 99%
“…In previous studies by the current authors [24,25], it was observed that an electrochemically formed tin oxide greatly reduced the growth of whiskers and that increasing the thickness of the tin oxide film promoted further reductions in whisker growth.…”
Section: Introductionmentioning
confidence: 73%
“…All surface modification treatments were carried out immediately after electrodeposition of the Sn or Sn-Cu coating using, if required, a Solartron SI 1286 Electrochemical Interface potentiostat and the 3-electrode cell described previously [24,25].…”
Section: Surface Modification Treatmentmentioning
confidence: 99%
See 1 more Smart Citation